The influence of patriarchal cultural factors on pregnancy complications (antepartum hemorrhage) at Mitra Medika General Hospital, Bandar Klippa, Indonesia - Simamora, Liyana; Ismah, Zata; Susilawati (Universitas Airlangga, 2024)
HIGHLIGHTS 1. Antepartum hemorrhage stands as one of the major contributors to maternal mortality globally. 2. Patriarchal culture is among the societal factors impacting maternal mortality rates.3. Patriarchal cultural factors associated with antepartum hemorrhage are examined to establish effective preventive measures. ABSTRACT Objectives: The objective of this study was to determine the influence of patriarchal culture on the occurrence of antepartum hemorrhage at Mitra Medika General Hospital. Materials and Methods: This study employed an analytical observational design with a case-control approach. The sample for this study included pregnant women in their third trimester and mothers who had given birth within a maximum of 4 months from the time of the study at Mitra Medika General Hospital, Bandar Klippa, Indonesia. There were 90 respondents, comprising 30 case groups and 60 control groups. The sampling method for the case group used quota sampling, while the control group utilized accidental sampling. The research instrument utilized questionnaires and secondary data (antepartum hemorrhage diagnoses). Data analysis employed the chi-square test for bivariate analysis and multiple logistic regression for multivariate analysis, with a significance level of 0.05. Results: There was a significant relationship between decision-making (p=0.030), family support (p=0.003), psychological domestic violence (p=0.024), and sexual domestic violence (p=0.039), no relationship with physical domestic violence (p=0.257) with the occurrence of antepartum hemorrhage. Multivariate analysis revealed that the family support variable was the most dominant risk factor with an Exp (B) value of 8.230 in causing antepartum hemorrhage. Conclusion: The patriarchal cultural factors that significantly affect antepartum hemorrhage at Mitra Medika General Hospital, Bandar Klippa, Indonesia, are decision-making, family support, psychological domestic violence, and sexual domestic violence.